2009
DOI: 10.1016/j.jcf.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous monthly pulse methylprednisolone treatment for ABPA in patients with cystic fibrosis

Abstract: High-dose IV-pulse methylprednisolone is an effective treatment for ABPA in CF with minor side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 27 publications
2
51
0
10
Order By: Relevance
“…All the reports were in patients with ABPA complicating cystic fibrosis, and involved both adult and paediatric patients (table 1). Three reports used pulse methylprednisolone 10-20 mg?kg -1 as a steroid sparing agent for three consecutive days every month [9,10,12]. One report involves the use of high-dose methylprednisolone in a life-threatening ABPA exacerbation unresponsive to oral steroid, which is similar to our cases [11].…”
Section: Pulse Methylprednisolone In Allergic Bronchopulmonary Aspergsupporting
confidence: 66%
See 1 more Smart Citation
“…All the reports were in patients with ABPA complicating cystic fibrosis, and involved both adult and paediatric patients (table 1). Three reports used pulse methylprednisolone 10-20 mg?kg -1 as a steroid sparing agent for three consecutive days every month [9,10,12]. One report involves the use of high-dose methylprednisolone in a life-threatening ABPA exacerbation unresponsive to oral steroid, which is similar to our cases [11].…”
Section: Pulse Methylprednisolone In Allergic Bronchopulmonary Aspergsupporting
confidence: 66%
“…Both the index cases failed to respond to high doses of oral steroids and itraconazole and were managed with intravenous methylprednisolone pulse therapy. A systematic review of the PubMed and EMBASE databases using the search terms: ''allergic bronchopulmonary aspergillosis'' OR ''abpa'' OR ''abpm'' OR ''allergic bronchopulmonary mycosis'' yielded four reports (39 cases) on the use of high doses of intravenous methylprednisolone in the management of ABPA [9][10][11][12]. All the reports were in patients with ABPA complicating cystic fibrosis, and involved both adult and paediatric patients (table 1).…”
Section: Pulse Methylprednisolone In Allergic Bronchopulmonary Aspergmentioning
confidence: 99%
“…Acute ABPA flares can be treated with intravenously administered pulsed methylprednisolone at 10-15 mg/kg/day for a three day period every month. 30,45 Methylprednisolone was administered to four CF-ABPA patients in this study and a trend towards reduction in Af-stimulated CD203c values was observed after treatment. However, this trend was not significant (P = 0.1604) warranting future longitudinal study with increased numbers to examine the effect of corticosteroid treatment on Af sensitization and potentially the use of the BAT to monitor treatment responses.…”
Section: Discussionmentioning
confidence: 74%
“…16,31 For this reason, identifying individuals with Af sensitization with or without ABPA is important to ensure appropriate and timely therapeutic intervention to minimize pulmonary impact. 30 In this study we focused on the basophil activation marker CD203c as an indicator of Af sensitization and assessed its effect on important clinical measures of CF disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation